Bioinformatics Tools in Agriculture: An Update - Zaynab, Madiha; Kanwal, Sonia; Abbas, Safdar; Fida, Fiza; Islam, Waqar; Qasim, Muhammad; Rehman, Nazia; Fida, Faiza; Furqan, Muhammad; Rizwan, Muhammad; Anwar, Muhammad; Hussain, Ansar; et al. (PSM Biological Research, 2017)
Bioinformatics plays an important role in agriculture science. As the data amount grows exponentially, there is a parallel growth in tools and methods demand in visualization, integration, analysis, prediction and management of data. At the same time, many researchers in the field of plant sciences are unfamiliar with available methods, databases, and tools of bioinformatics which could lead to missed information opportunities or misinterpretation. Some key concepts of software packages, methods, and databases used in bioinformatics are described in this review. In this review, we have discussed some problems related to biological databases and biological sequence analyses. Gene findings, genome annotation, type of biological database, how to data represent and store was deliberated. Future perspective of bioinformatics tools was also discussed in this review.